Readiness of State Madrasah Ibtidaiyah for ANBK Implementation: Between Government Policy and Field Reality - Rifqotul Aulia; Syarifatul Fitri Hidayah; Intan Aulia Rakhmawati; Herman Khunaivi; Ahmad Sunoko; Sarah Ainun Nisak (Institut Agama Islam Negeri Palangka Raya, 2025)
This study was conducted based on observations of school readiness in implementing ANBK assessments at state elementary madrasahs in Rembang Regency. This study aimed to determine the implementation, obstacles, and solution readiness of infrastructure, human resources, and administration of the implementation of ANBK 2022 at the State Madrasahs Ibtidaiyah level in Rembang Regency. This study used descriptive research with a qualitative approach. The subjects of the study were the principals, teachers, proctors, and students. Data collection techniques included observation, interview, and documentation. This study's results demonstrated schools' readiness to implement ANBK in 2022. 1), the schools provided adequate information and communication technology facilities by the 2022 Standard Operating Procedures (SOP). 2), sufficient financial resources were available to support implementation. 3), the assessment rooms were adequate. 4), the principals actively fulfilled their roles in the national assessment. 5), the teachers showed good technical readiness as participants in the national assessment. 6), the students also demonstrated strong technical readiness. 7), the proctors, technicians, and supervisors carried out their duties and responsibilities effectively. 8), the schools formed specific ANBK implementation teams. 9), the schools did not have special learning resources to support ANBK. Finally, the implementation teams overcame several technical obstacles. Although the schools had completed the preparation, they encountered challenges such as limited computer availability and server problems. The teachers solved these issues by borrowing additional computers or laptops from colleagues.